2016
DOI: 10.1073/pnas.1515380113
|View full text |Cite
|
Sign up to set email alerts
|

Songbirds use spectral shape, not pitch, for sound pattern recognition

Abstract: Humans easily recognize "transposed" musical melodies shifted up or down in log frequency. Surprisingly, songbirds seem to lack this capacity, although they can learn to recognize human melodies and use complex acoustic sequences for communication. Decades of research have led to the widespread belief that songbirds, unlike humans, are strongly biased to use absolute pitch (AP) in melody recognition. This work relies almost exclusively on acoustically simple stimuli that may belie sensitivities to more complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 63 publications
3
69
0
Order By: Relevance
“…In fact, in a follow-up study with humans and chickadees, we found that chickadees did not respond to novel timbres based on the pitch information with which they had been trained (Hoeschele, Cook, Guillette, Hahn, & Sturdy, 2014). Similar results have also been found in starlings (Bregman, Patel, & Gentner, 2016).…”
Section: Relative Pitch What Is Relative Pitch?supporting
confidence: 82%
See 1 more Smart Citation
“…In fact, in a follow-up study with humans and chickadees, we found that chickadees did not respond to novel timbres based on the pitch information with which they had been trained (Hoeschele, Cook, Guillette, Hahn, & Sturdy, 2014). Similar results have also been found in starlings (Bregman, Patel, & Gentner, 2016).…”
Section: Relative Pitch What Is Relative Pitch?supporting
confidence: 82%
“…A similar result was found in European starlings: They also did not do well on traditional laboratory relative pitch tasks but readily recognized transposed versions of their own song (Bregman, Patel, & Gentner, 2012). However, it is likely that they were not directly using pitch in this task but spectral shape information from which both pitch and timbre are derived (Bregman et al, 2016).…”
Section: Relative Pitch What Is Relative Pitch?supporting
confidence: 60%
“…Recent experimental studies show that birds are more sensitive to similarities and differences in spectral shape than was previously assumed (Bregman et al, 2016;Hoeschele et al, 2014). Chickadees, in particular, appear to find relative differences in the amplitudes of frequencies produced within fee-bee songs to be highly salient (Hoeschele et al, 2014).…”
Section: Perception Of Changes In Singer Distancementioning
confidence: 92%
“…Humans have been tested on their ability to detect differences in the intensities of two simultaneously presented tones centered at different frequencies, however (Dai & Green, 1992;Feth & O'Malley, 1977;Versfeld & Houtsma, 1995). Such distinctions can be viewed as a special case of profile analysis (Green, 1987), which is closely related to auditory discrimination of spectral shape (Bernstein & Green, 1988;Bregman, Patel, & Gentner, 2016;Langemann, Zokoll, & Klump, 2005). Profile analysis involves detecting an absolute increment in the amplitude of one tonal signal among a background of other tonal signals.…”
Section: Perception Of Changes In Singer Distancementioning
confidence: 99%
“…As has been shown by Bregman, Patel, and Gentner (2016), birds (European starlings) rely on acoustic cues other than absolute pitch to generalize to novel stimuli. Instead of using the absolute frequency of the sounds, they prioritize their spectral shape.…”
Section: Experience and The Emergence Of Consonance Preferencesmentioning
confidence: 96%